Methanotroph-microalgae co-culture for greenhouse gas mitigation: Effect of initial biomass ratio and methane concentration. (November 2020) - Ruiz-Ruiz, Patricia; Gómez-Borraz, Tania L.; Revah, Sergio; Morales, Marcia
Abstract: This work evaluated the effect of different initial biomass ratios in a co-culture of an alkaliphilic methanotrophic bacteria consortium (AMB) and the green microalga Scenedesmus obtusiusculus (GM) on the maximum CH4 specific biodegradation rate and global carbon uptake. The highest maximum specific biodegradation rate was 589 ± 0.01 mgCH4 gbiomass −1  d −1 obtained for a proportion of 3:1 AMB-GM (w w −1 ) and 8% of initial CH4 in the headspace. The methane degradation rate was 1.5 times lower than the value obtained solely by the AMB consortium, and it was associated with pH increases due to the evolved CO2 consumption by the microalga. Increased activity of the AMB consortium along the experiments was due to progressive adaptation. Massive sequencing revealed the presence of methanotrophic/methylotrophic species such as Methylocystis sp., Methylomicrobium sp., Methylophaga sp., and Hyphomicrobium sp. Successful complete methane and carbon dioxide uptake was obtained with the 3:1, 4:1, and 5:1 AMB-GM biomass ratios, while for the rest of the ratios tested, more than 70% of the initial methane was transformed into biomass and inorganic carbon. This study showed that methanotrophic-microalgal co-cultures lead to a promising strategy for greenhouse gases mitigation in one step. Graphical abstract: Image 1 Highlights: Different ratios of methanotrophs and microalgae were tested in co-culture. Complete CH4 and CO2 mitigation was found with initial 4 and 8% CH4 concentrations. rRNA sequencing revealed the presence and evolution of methanotrophic populations. pH increased during cultivation and needs regulation to maintain microbial activity.